Nośność graniczna płyt w kształcie trójkąta równoramiennego - Kleiber, M.; Kwieciński, M. (Engineering Transactions, 1969)
In the paper a kinematic analysis has been conducted of the problem of limit load of plates in the shape of equilateral triangles, loaded in a continuous and concentrated way. Hitherto known solutions have been systemized and completed. The values of the limit loads have been given for plates with the following boundary conditions: free edge, simple support, built-in edge. The obtained results are an upper bound to the exact limit loads.